(untitled) (Physical Education, Health and Social Sciences, 2025)
This research aimed to examine ESL undergraduate learners metacognitive reading strategies use and their relationship with reading comprehension. The study’s basically based on how frequently three subcategories of reading strategies global reading strategies (GRS), Problem Solving Reading Strategies (PSRS), and Support Reading Strategies (SRS) were employed while academic reading within an ESL setting at university of Sindh Jamshoro. The quantitative correlational research design was used to gather data from respondents, pilot study was conducted before main study. The study comprises of 200 undergraduate learners, involving 110 males 90 females. The study used Survey of Reading Strategies (SORS) formulated by Kouider Mokhtari and Ravi Sheorey along with IELTS academic reading comprehension test, which is selected based on participant’s proficiency level. The metacognitive strategies on SORS were scored on 1-5 likert scale. The quantitative data was analyzed through SPSS (Statistical Package for Social Sciences) 22 version. The found findings of this research reveals that learners used three categories which are global reading strategies (GRS), problem solving reading strategies (PSRS), support reading strategies (SRS). Furthermore, most frequently used metacognitive strategy was Global reading strategy (GRS), then problem solving reading strategies and (PSRS), support reading strategies (SRS). In addition, current study also reveals that there is significant relationship between metacognitive reading strategies use and English reading comprehension.